Nursing postgraduates’ innovative behaviour, influencing factors and educational requirements: a national cross-sectional study - Jiayi Zhu; Shuai Yuan; Lihui Pu; Ruben Martin-Payo; Liqin Wei; Mengying Qiu; Fengying Zhang (BMC Medical Education)
Abstract Background Innovative behaviours are important for nursing postgraduates who are a significant reserve for future nursing career, thinking critically, utilizing technologies and solving complex problems. In nursing undergraduates’ education, innovative behaviour is closely linked with the development of professional identity. However, there are limited studies exploring innovative behaviours, influencing factors and educational requirements of nursing postgraduates. Aim To investigate nursing postgraduates’ innovative behaviour, influencing factors, and the correlation between innovative behaviour and professional identity. Moreover, exploring nursing postgraduates’ requirements for innovational education. Methods A national descriptive cross-sectional study was conducted among postgraduate students in Chinese nursing schools between October and November 2022. A general information questionnaire, The Nurses’ Innovative Behaviour Scale, the Professional Identity Questionnaire for Nurse Student, and a multiple-choice question about students’ innovation education requirements were collected. The independent-sample t-test, one-way analysis of variance (ANOVA), multiple linear regression, and Pearson’s correlation analyses were conducted. Results This study recruited 426 nursing postgraduates from 44 nursing schools across China. The mean score of innovative behaviour of nursing postgraduates was 38.96 ± 4.90 (min-max 10–50). Nursing postgraduates’ professional identity was positively correlated with innovative behaviour (r = 0.436, P < 0.01). Participants who read scientific literature frequently, had a high level of professional identity, and grew up in urban areas had high levels of innovative behaviour (adjusted R 2  = 0.244, P < 0.001). Conclusions It was determined that the level of innovative behaviour is associated with their professional identity and the frequence of reading scientific literature in nursing postgraduates. It is imperative for educators to foster an environment that encourages postgraduate nursing students to engage with a wider array of scholarly literature and elevates postgraduate nursing students’ professional identity. Furthermore, the dissemination of advanced knowledge and the adoption of diverse pedagogical approaches are likely to meet the innovative demands of nursing postgraduates.